Menjernihkan Posisi Hijab Sebagai Kritik Ekspresi Keagamaan Fundamentalisme Islam - Mubaidi Sulaeman (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2020)
Based on the normative thought of Islamic fundamentalism who have textual tendencies and what they are in applying the arguments of theIslamic law, often ignoring the history of the emergence of a obligation provision, one of which is the law concerning muslimah hijab obligation.Therefore, Islamic fundamentalizm, hijab is obligated, even obligatory to cover its face and palms. Whereas for historians, the generalization of hijaborder against every muslimah is wrong because the hijab is cultural expression that owned by people outside the Arab peninsula and pre-Islam. So that hijab is historically not entitled to be claimed as a culture bornof Islamic alone.